The Impact of Tourism Products and Services on Satisfaction and Loyalty of Tourists Visiting Mertasari Beach Sanur Bali - Satia Negara, I Made Weda; Marina, Marina; Selamet, I Wayan Agus; Sri Mirayani, Ni Kadek; Paristha, Ni Putu Tiya (Akademi Komunitas MAPINDO, 2023)
Industrial activities require hard work to succeed, which will provide a number of products that will provide satisfaction and welfare to humans. That is why the word industry always implies a business that produces products. The product is a series of services that have economic, social, and psychological aspects. In research that has been carried out on Mertasari Beach Sanur Bali with the aim of research to determine the effect of tourism products and services on satisfaction and to analyze the effect of service and satisfaction on the loyalty of tourists visiting Mertasari Beach. The research method used in this research is quantitative method using smartPLS 4.0 as a medium for analyzing data, data sources in this study from primary and secondary data and data collection methods in this study with observation, questionnaires and documentation along with interviews, the location of this research was carried out at mertasari beach sanur bali with a period from March 2023 to October 2023. The results in this study indicate that Based on the abstract of this study, it can be concluded that tourism products and satisfaction have a significant influence on the loyalty of tourists visiting Mertasari Beach Sanur Bali. In addition, service variables and satisfaction have a significant influence on the loyalty of tourists visiting Mertasari Beach Sanur Bali. Tourism products offered to tourists also have a significant influence on the loyalty of tourists visiting Mertasari Beach, Sanur Bali. When tourists are well served and receive services that meet their needs, they tend to feel satisfied. Keyword: Tourism Products_Tourist Satisfaction_Visiting Mertasari Beach